AN EVALUATION OF THE JOB SATISFACTION LEVELS OF TURKISH PROVINCIAL FOOTBALL REFEREES - Coban, Bilal (Soc Personality Res Inc, 2010)
This study was conducted in order to determine the job satisfaction levels of provincial referees on the basis of 9 demographic variables. The study sample consisted of 83 provincial referees working in Kahramanmaras, Adana, and Osmaniye provinces of Turkey. The Minnesota Satisfaction Questionnaire (MSQ; Dawis, Weiss, England, & Lofquist, 1967) was used to identify job satisfaction levels. While a statistically significant difference was found between provincial referees in terms of age, foreign language level, income level, and other-than-refereeing jobs and term (p < 0.05); no statistically significant difference was found between the provincial referees in terms of marital status, education level, and sports background (p < 0.05). It is recommended that mental and psychological needs of referees be met to ensure that they can perform well. Moreover, management and senior colleagues should support younger and less experienced referees.
Keywords: provincial referee; job satisfaction; intrinsic satisfaction; extrinsic satisfaction; foreign language fluency